Coupled thermo-mechanical modeling of drilling of multi-directional polymer matrix composite laminates. (May 2022) - Kubher, Sagar; Gururaja, Suhasini; Zitoune, Redouane
Abstract: The influence of in-situ cutting temperature on machining induced damage and machining forces during drilling of multi-directional carbon fiber reinforced polymer (MD-CFRP) composites has been examined using a coupled thermo-mechanical finite element (FE) framework. The MD-CFRP laminate has been modeled ply-by-ply as an equivalent homogeneous anisotropic material (EHM) using temperature dependent laminate elastic and fracture properties. Stress-based criteria has been adopted for element deletion simulating the drilling process. The intralaminar damage model for simulating various composite machining induced damage modes was implemented in the FE framework via a user material subroutine. A new composite damage criterion is proposed that accounts for the out-of-plane drilling damage behavior along tool feed direction. Additionally, a fracture mechanics approach has been used to simulate interlaminar delamination onset using surface based cohesive elements at the drill exit plies. The current numerical model predictions show a good agreement with drilling experiments for thrust force, delamination damage, and in-situ cutting temperature.